Subuh Orchestra of Religious Harmony of Baitunnur Mosque and Santo Yusuf Catholics Church in Pati Central Java - Zahra, Fathimatuz -; Basri, Muhammad Hasan; Arifin, Zainul -; Surachman, Anista Ika (FIKRAH, 2022)
This article discusses religious harmony in Pati, Central Java, related to mosques and churches in one location. This harmony was awakening through the combination of the sound of church bells and the sound of the recitation in the mosque using loudspeakers to create harmony between the two houses of worship. Purposing of this article was to narrate and discuss the harmony that occurred in Pati by conducting interviews with Catholic religious leaders, Muslim religious leaders, and residents of Arab, indigenous, and Chinese descent. This study focuses on three questions (a) How are religious symbols in religious harmony; (b) How to build harmony with religious symbols in the form of church bells and adhan); (c) How the Subuh orchestra as a symbolic sacred call for people who perform rituals in the mosque called the call to prayer and in churches use church bells to signify the morning sacrament. The result of this research was that religious people build religious harmony through the dawn of this orchestra, making this simple culture a unifying tool for diversity in society.